Muslim friendly medical services quality, satisfaction and loyalty intention: Perspective of Muslim patients at the private hospitals / Muhammad Khalilur Rahman - Muhammad Khalilur , Rahman (2019)
The Muslim-friendly medical services quality is a new mode of medical services which aims to fit the Muslim’s medically oriented social development and extend the reform of the medical care system. Past studies on this topic have focused mainly on the popular discourse of generic medical service quality. There has been little knowledge available focusing on the niche market of Muslim-friendly medical services quality, especially in the area of satisfaction and loyalty intention with medical services at private hospitals. This study aims to investigate the influence of six major antecedents (i.e. Shariah amenities, physicians’ services, nurses’ services, healthcare technicality, hospital environment and administrative behaviour) on Muslim patients’ satisfaction and their loyalty intention at hospitals in Malaysia. It also examines the mediating role of the Muslim patients' satisfaction in the relationships between the Muslim-friendly medical services quality and patients' loyalty intention. Empirical data were collected using a self-completed survey questionnaire and respondents were chosen using random samplings from various clinics for out-patients and wards for inpatients in fifteen private hospitals in Klang Valley and were analysed by using the structural equation modelling technique through moment structure (AMOS). The results showed that administrative behaviour, nurses’ services and Shariah amenities have highly significant relationships with satisfaction followed by healthcare technicality, hospital environment and physicians’ services. Muslim patients’ satisfaction has a significant relationship with their loyalty intention. Administrative behaviour, physicians’ services and healthcare technicality have direct and positive significant relationships with loyalty intention, while, Shariah amenity has a negative significant relationship. Patients’satisfaction fully mediates the relationship between Shariah amenities and loyalty intention. Patients’ satisfaction partially mediates the relationships between physicians’ services, nurses’ services, healthcare technicality, hospital environment, administrative behaviour and loyalty intention. The results have important implications for product development and managerial considerations of hospitals. Service providers need to be mindful that all aspects of Muslim-friendly medical services quality are important and need to be delivered satisfactorily to ensure customer satisfaction. Patients’ satisfaction is a crucial bridge in determining the likelihood of future return among Muslims patients to the hospitals.